2016
DOI: 10.17957/ijab/15.0152
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming with Extracts of two Seaweeds Alleviates the Physiological and Molecular Impacts of Salinity Stress on Radish (Raphanus sativus)

Abstract: To cite this paper: Kasim, W.A., K.M. Saad-Allah and M. Hamouda, 2016. Seed priming with extracts of two seaweeds alleviates the physiological and molecular impacts of salinity stress on radish (Raphanus sativus AbstractSeeds of radish were primed with the extract of either Codium taylorii or Pterocladia capillacea for 2 h, then sown in claysandy soil and left to grow under the effect of either 150 or 200 mM NaCl, however the control treatment was irrigated only with tap water, for 35 days. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 27 publications
(27 reference statements)
2
10
1
Order By: Relevance
“…Proline accumulation is a sensitive physiological index of plant response to various abiotic stresses and plays a positive role in the salt tolerance mechanisms of many crops by contributing to membrane stability (Ashraf & Harris, 2004). In contrast to the results of our study where we found a slight non-significant increase of Kasim et al (2016), on radish (Raphanus sativus). Similarly, our results are consistent with those of Aziz et al (2011) and Latique et al (2013) on Amaranthus tricolor and common bean (Phaseolus vulgaris), respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Proline accumulation is a sensitive physiological index of plant response to various abiotic stresses and plays a positive role in the salt tolerance mechanisms of many crops by contributing to membrane stability (Ashraf & Harris, 2004). In contrast to the results of our study where we found a slight non-significant increase of Kasim et al (2016), on radish (Raphanus sativus). Similarly, our results are consistent with those of Aziz et al (2011) and Latique et al (2013) on Amaranthus tricolor and common bean (Phaseolus vulgaris), respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Several authors such as (Ahmad et al, 2013;Buchanan et al, 2000;Kasim et al, 2016) have shown that algae maintain membrane integrity by reducing electrolyte leakage. The results of the study of Semida and Rady (2014) showed that soaking bean seeds in propolis or maize seed extract increased the membrane stability index, while reducing membrane lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our results, plants subjected to salinity stress either showed a decrease in proline content or the content was not significantly affected. This may be attributed to the replacement of proline by another osmoregulator compound under salinity stress [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Still, the treatment had no significant effect on germination rate when plants were subjected to different concentrations of NaCl (from 5 mmol.L −1 to 50 mmol.L −1 ). However, priming radish seeds subjected to 150 mM and 200 mM NaCl with Codium taylorii or Pterocladia capillacea extracts induced molecular changes in the DNA patterns of the plant by the disappearance of some bands and the appearance of other ones [62].…”
Section: Biostimulant Properties Of Seaweed Extract Are Emphasized Unmentioning
confidence: 99%